Revised systematics of Fabricia oregonica Banse, 1956 (Polychaeta: Sabellidae: Fabriciinae): an example of the need for a uninomial nomenclatural system - Fitzhugh, Kirk (Zootaxa, 2010)
Previous descriptions of members of Fabricia oregonica Banse, 1956, have distinguished it by the presence of only narrowly hooded inferior thoracic notochaetae, in contrast to the presence of pseudospatulate chaetae in median chaetigers of the type species, F. stellaris (Müller, 1774). In other respects, past descriptions of specimens to which F. oregonica refers have lacked the necessary detail to clearly determine generic placement, and the type material is in poor condition. Recently collected specimens matching earlier descriptions are used to redescribe members of the species. An exclusive sister-group relationship does not exist between F. stellaris and F. oregonica, precluding the latter species being assigned to Fabricia. Fabricia oregonica is therefore placed in a new genus, Bansella. Under the view that all taxa, whether phylogenetic or specific, are explanatory hypotheses, it is pointed out that the monotypic Bansella cannot be defined as such a hypothesis. While the International Code of Zoological Nomenclature requires that names be defined by way of ‘differentiating characters,’ this approach is at odds with the scientific endeavor of biological systematics to infer explanatory hypotheses, colloquially known as taxa. In addition to only having narrowly hooded inferior notochaetae, members of B. oregonica differ from F. stellaris specimens in having abdominal uncini with a much shorter manubrium. The ventral, lobe-like collar in B. oregonica specimens is also distinctly rectangular as opposed to triangular. Members of the two species are similar in that females have pigmented spermathecae in the bases of branchial lobes and spermiogenesis occurs in males in chaetigers 3–8.